2020
DOI: 10.1021/acsaem.0c01403
|View full text |Cite
|
Sign up to set email alerts
|

High Discharge Energy Density and Efficiency in Newly Designed PVDF@SiO2–PVDF Composites for Energy Capacitors

Abstract: The fabrication of a core–shell structure is an effective method of obtaining a composite film with a high energy density. Herein, we prepared a new type of composite film with high energy density and energy efficiency by using silica-coated core–shells on poly­(vinylidene fluoride) (PVDF) particles that comprised a high proportion of polar phases rather than inorganics with high dielectric constants. We prepared PVDF particles with a high proportion of the β-phase using emulsion polymerization. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…To make a more comprehensive comparison of the energy storage properties between inorganic filler/polymer matrix composites and the all-organic composite, relevant studies are shown in Figure . , The breakdown strength of the inorganic filler/polymer matrix composites is mostly concentrated below 550 kV mm –1 with a lower energy storage efficiency, as shown in Figure , which is greatly related to the defects generated by the introduction of inorganic fillers. The all-organic composite in this work can effectively avoid the generation of similar defects, achieve a higher breakdown strength, and maintain high efficiency, which makes it have a higher energy storage density although without a higher dielectric constant like inorganic filler/polymer matrix composites.…”
Section: Resultsmentioning
confidence: 99%
“…To make a more comprehensive comparison of the energy storage properties between inorganic filler/polymer matrix composites and the all-organic composite, relevant studies are shown in Figure . , The breakdown strength of the inorganic filler/polymer matrix composites is mostly concentrated below 550 kV mm –1 with a lower energy storage efficiency, as shown in Figure , which is greatly related to the defects generated by the introduction of inorganic fillers. The all-organic composite in this work can effectively avoid the generation of similar defects, achieve a higher breakdown strength, and maintain high efficiency, which makes it have a higher energy storage density although without a higher dielectric constant like inorganic filler/polymer matrix composites.…”
Section: Resultsmentioning
confidence: 99%
“…6 In particular, polymer nanocomposites have been considered as promising candidates to achieve high dielectric constant (3 r ) and electric breakdown strength (E b ), low loss tangent (tan d), easy fabrication process, low cost, and excellent exibility in the advancement of market electronics. [7][8][9][10] In this regard, poly(vinylidene uoride) (PVDF) is a well-known thermoplastic polymer because of its tunable properties such as exibility, robustness, cost-effectiveness and easy processing. Generally, PVDF has 4 different polymorphs, i.e., a-, b-, gand d-phases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dielectric films based on these fluororesins show high discharge energy density. However, the high dielectric loss, remnant polarization, and low charge–discharge efficiency of these films lead to decreased discharge energy density, which limits the application of PVDF in the thin-film capacitor field. …”
Section: Introductionmentioning
confidence: 99%